Penerapan Model Pembelajaran Problem Based Learning (PBL) untuk Meningkatkan Kemampuan Pemecahan Masalah Peserta Didik Pada Materi Asam Basa - Pratiwi, Dini Eka; Erna, Maria; Anwar, Lenny (FKIP University of Mataram, 2025)
This study aims to determine the improvement of students’ problem-solving abilities in acid-base material through the application of the Problem Based Learning (PBL) learning model in class XI of SMAN 7 Pekanbaru. This study uses a quantitative method with a one-group pretest-posttest pre-experimental design. The population in this study were All students of class XI of SMAN 7 Pekanbaru. The research sample was 36 students selected through a simple random sampling technique. The instrument used was a problem-solving ability test validated by 3 validators. Data analysis through normality tests, paired sample t-tests and N-Gain tests. The results showed that there was a significant increase in students’ problem-solving abilities after the application of the PBL model, indicated by the calculated t value > t table (25.983 > 2.03011) and an average N-Gain value of 0.71 with a high category. These results indicate that the PBL model is effective in improving students’ abilities in understanding, planning, and implementing problem solving in acid-base material.